ANALISIS PERMAINAN TRADISIONAL DAKON DALAM MELATIH KONSEP BERHITUNG DASAR DI TAMAN KANAK KANAK - Martiyadi Nurhidayat; Tiphanny Aurumajeda (Universitas Bhinneka PGRI, 2025)
Students' difficulties in understanding simple arithmetic concepts, such as addition and subtraction, are often caused by lack of concentration, being easily distracted, excessive use of gadgets, and minimal public facilities for social interaction. This study uses a qualitative approach with a case study to understand this phenomenon in depth. The design thinking method is applied to design solutions, while effectiveness testing is carried out using a pretest-posttest one group design equipped with a semantic differential scale to measure student responses. The results of the study showed that conventional methods such as the use of LKS produced an average pretest score of 20 out of a maximum of 40. After treatment using dakon learning media, the posttest score increased significantly to 37 out of a maximum of 40. Dakon media also shortens the duration of learning and makes it easier for students to understand concepts. Based on the semantic differential scale, most respondents gave high scores on the aspects of fun, enthusiasm, and positive impact. The discussion of the results confirmed that dakon as a traditional game is effective in increasing concentration, facilitating understanding, and creating an interactive learning atmosphere. In conclusion, dakon is an innovative learning media that is fun and effective for early childhood, and is able to reduce dependence on gadgets and support more meaningful learning.